Presbyopia-Correcting Intraocular Lenses Implantation in Eyes After Corneal Refractive Laser Surgery: A Meta-Analysis and Systematic Review - Sun, Yang; Hong, Yingying; Rong, Xianfang; Ji, Yinghong (Frontiers in Medicine, 2022)
Purpose To assess the efficacy, safety, and predictability of presbyopia-correcting intraocular lenses (IOLs) in cataract patients with previous corneal refractive surgery. Methods A systematic literature search was performed to identify studies evaluating the clinical outcomes of presbyopia-correcting IOLs implantation in cataract surgery after laser refractive surgery. Outcomes were efficacy, safety and predictability parameters. Results The authors identified 13 studies, involving a total of 128 patients and 445 eyes. Presbyopia-correcting IOLs were effective at improving distance, intermediate and near visual acuity aftercataract surgery. The proportion of post-laser surgery eyes with uncorrected distance visual acuity (UDVA) ≥ 20/25 was 0.82 [95% confidence interval (CI), 0.74-0.90] and the pooled rates of spectacle independence at near, intermediate, and far distances were 0.98 (95% CI, 0.94-1.00), 0.99 (95% CI, 0.95-1.00) and 0.78 (95% CI, 0.65-0.94) respectively. The percentage of participants who suffered from halos and glare was 0.40 (95% CI, 0.25-0.64) and 0.31 (95% CI, 0.16-0.60), respectively. The predictability had a percentage of 0.66 (95% CI, 0.57-0.75) and 0.90 (95% CI, 0.85-0.96) of eyes within ±0.5 diopters (D) and ±1.0 D from the targeted spherical equivalent. Conclusions Presbyopia-correcting IOLs provide satisfactory results in terms of efficacy, safety and predictability in patients with previous corneal refractive surgery, but have a higher risk of photopic side effects such as halos and glare.